A rare case of prostate cancer with spontaneous gingival bleeding as the initial manifestation of underlying disseminated intravascular coagulation. Issue 1 (26th March 2022) - Tanaka, Takuya; Fukuma, Daiki; Yuno, Akira; Nakamoto, Masafumi; Imamura, Takahisa; Nakayama, Hideki
Abstract: Background: Gingival bleeding is uncommon in disseminated intravascular coagulation (DIC), rarely caused by prostate cancer (PC). Case presentation: A 69‐year‐old man complained of uncontrollable gingival bleeding. A low platelet count and prolonged bleeding and prothrombin times were observed. Elevated levels of fibrin degradation products, D‐dimer, thrombin‐antithrombin‐complex, plasmin‐α2 ‐plasmin inhibitor‐complex, and prostate‐specific antigen suggested PC‐associated DIC with hyperfibrinolysis. Computed tomography revealed prostate tumor with metastasis to the regional lymph nodes and vertebrae. By treatment with heparin, anti‐androgenic agents, and tranexamic acid, gingival bleeding resolved. Conclusion: Oral and maxillofacial surgeons should be aware that gingival bleeding may be a sign of PC‐associated DIC.